2018
DOI: 10.21580/ihya.20.1.2729
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendapatan Bagi Hasil dan Pemberian Bonus terhadap Loyalitas Nasabah di Bank Syariah Mandiri Kantor Cabang Sangatta

Abstract: <p>This type of research is descriptive quantitative. This study uses analytical techniques that include path analysis with the aim to find out the direct and indirect influence of independent variables on the dependent variables processing data using SPSS, simultaneous testing (F test) and individual testing (t test). The population in this study are customers in Bank Syariah Mandiri Sangatta Branch Office. And the number of samples taken by 98 respondents by using random sampling technique. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Customers that are satisfied with the profit-sharing system tend to continuously use the banking products and services and even advise others to use them. Khairi et al (2018) showed that profit-sharing positively affects customers' loyalty to an Islamic bank. Therefore, the first hypothesis is proposed as follows: H1: Profit-sharing positively affects customers' loyalty to Islamic banks.…”
Section: Hypothesis Development the Influence Of Profit-sharing On Cu...mentioning
confidence: 99%
See 3 more Smart Citations
“…Customers that are satisfied with the profit-sharing system tend to continuously use the banking products and services and even advise others to use them. Khairi et al (2018) showed that profit-sharing positively affects customers' loyalty to an Islamic bank. Therefore, the first hypothesis is proposed as follows: H1: Profit-sharing positively affects customers' loyalty to Islamic banks.…”
Section: Hypothesis Development the Influence Of Profit-sharing On Cu...mentioning
confidence: 99%
“…The bank is one of the financial institutions that have an important role in people's economic activities because it serves as an intermediary between parties with a surplus of funds (Khairi, Nursalim, & Parno, 2018). In Indonesia, Islamic banks give the option to society to either save or finance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations